Railway Noise at Gubeng Station: Assessing Railway Noise at Gubeng Station: Assessing Sources, Levels, and Health Sources, Levels, and Health Implications for Passengers - Yusran, Yosef; Azizah, R; Khoirun Nisa, Nahdhiah; Warjo, Yopi Riski Mei Sandra; Muflihah, Asriani (Dian Nuswantoro Semarang, 2025)
Rail transportation is a preferred mode of transport for the public due to its various advantages; however, it creates environmental issues in the form of noise pollution, which has the potential to impact health and comfort. This study aimed to measure the noise levels at Gubeng Station in Surabaya and analyze their compliance with applicable quality standards. Using an observational quantitative method, measurements were taken at 10 representative points within the station on April 17, 2025, employing a Sound Level Meter (SLM) in accordance with SNI 8247:2017. The results indicate that noise levels varied, with the highest value of 89 dBA in the train engine area, exceeding the safe limit for an 8-hour work exposure stipulated by Minister of Manpower Regulation No. 13/MEN/X/2011. The majority of measurement points, such as the departure platform (78.5 dBA) and the waiting room (77 dBA), also surpassed the environmental quality standard of 60 dBA regulated by Minister of Health Regulation No. 2 of 2023, although they remained below the Threshold Limit Value (TLV) for workers. Only the Old Gubeng waiting room (58.2 dBA) met the Ministry of Health standard. This study concludes that while the noise at Gubeng Station remains safe for workers regarding short-term exposure, the conditions have the potential to cause discomfort and health risks for passengers and the general public. Comprehensive mitigation measures, including the installation of sound dampeners, waiting room zoning, and the use of Personal Protective Equipment (PPE), are required to create a healthier and more comfortable station environment.